The influence and impact of the exchange rate on the economy - Zhao, Yuxin (2020)
This paper analyzes the influence and impact on the exchange rate from several aspects. Firstly, the primary factors influenced by the exchange rate, export, the prices and costs are introduced in this paper. Productivity refers to the increase because the local currency strengthens. Then, it indicates that the exchange rate affects productivity. The last part about influential factors is the effect on the number of tourists. After analyzing the impact of the exchange rate, some suggestions about exchange rate policies are put forward. The exchange rate is an essential element, and it requires to attach importance to both the logical operation and the appropriate use of policy.